DENSIFICATION PROCESS AND PROPERTIES OF DIAMOND/SiC COMPOSITES BY PRESSURELESS VAPOUR INFILTRATION - Xulei Wang; Pengfei Zhu; Liu Pengfei; Jiao Sijia; Ding Yunpeng; He Xinbo (Ceramics-Silikáty, 2023)

(untitled)
Diamond/silicon carbide (SiC) composites with different diamond contents were prepared by pressureless silicon (Si) vapour infiltration. The densification process of the Si infiltration of the composites was analysed. Three densification process were put forward. The densification degree of the composites was determined by the concentration of the Si vapour. The three-dimensional skeleton of the SiC composite embedded with diamond constitutes the best path for the heat conduction of composites. With an increase of diamond content, the thermal conductivity (TC) of the composites increases at first and then decreases, reaching a maximum value at a diamond 60 vol.%, with the TC of 536 W/(m·K). In the temperature range of 50~500 °C, the thermal expansion coefficient of the composite varies from 1.0 to 3.25 ppm/K. The bending strength of the composite reached a maximum value of 334.52 MPa. The composite has a low thermal expansion coefficient, superior thermal conductivity and bending strength, and can be used as an alternative thermal management material.